التناص الأدبي في مسرحية "محمد صلى الله عليه وسلم" لتوفيق الحكيم - Nisa', Kholifah Wahidatun (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2022)
One of the Egyptian famous writer is Taufiq Al-Hakim. Of the many drama scripts that he wrote, namely "Muhammad SAW" which is a biography of the life of the Prophet SAW which is outlined in the form of a drama. Of course a writer has the inspiration to be the main idea during the writing of his literary work. This is what is commonly referred to as intertextual. The problems examined in this research are: First, what are the forms of intertext in the drama script "Muhammad SAW" by Taufiq Al-Hakim? Second, what are the influences that arise on the drama script "Muhammad SAW?. The method used in this research is a qualitative descriptive method with a literature study approach. From the research results, it is founded that in the drama script "Muhammad SAW" there are 22 direct intertext and 9 indirect intertext. As for the influence of the previous texts on the drama script "Muhammad”, namely the value of the Islamic religion and the Al-quran as the foundation of drama script writing.